Management for Improving the Quality of Student Learning in Primary Schools - Maryati, Susri; Ahmad, Syarwani; Eddy, Syaiful (Journal of Social Work and Science Education, 2020)
This study determined the implementation of learning management used by teachers in improving student achievement. The data collection methods are observation, interview and documentation, then checking the validity of the data by comparing the information provided by the informant and the observation data with the results of the interview, then the data is analyzed qualitatively. From the results of the study, it was found that: 1) the implementation of learning management by teachers in improving student achievement was carried out by identifying, objectives, benefits, planning steps, planning stages, including indicators or quality targets to be achieved as a process of increasing learning achievement students in order to realize the quality of education; 2) the inhibiting factor for the implementation of learning management at SDN in Babat Toman Subdistrict, Musi Banyuasin Regency, namely the lack of awareness of teachers to compile lesson plans, many students are passive in implementing learning even though they have been given a stimulus by the teacher and the lack of variation in assessments carried out by the teacher and too many students so the time allocation for conducting the assessment is insufficient or difficult; 3) a solution to overcoming obstacles, namely by conducting trainings on how to compile a good syllabus and lesson plans applying learning strategies that are evaluated by varying assessment techniques.